2009
DOI: 10.1136/hrt.2009.169896
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiplatelet therapy for more than 12 months after percutaneous coronary intervention: insights from the Guthrie PCI Registry

Abstract: In patients who undergo successful native coronary PCI and survive event-free for at least 12 months, continuation of dual antiplatelet therapy beyond 12 months does not confer long-term protection from death or MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Harjai et al [44] in a prospective observation, demonstrated that the continuation of DAPT beyond 12 months in patients undergoing PCI of native coronaries, who survived with no major adverse cardiac events (MACE), did not confer long-term protection from death or myocardial infarction. Ferreira-Gonzales et al [45] has suggested that the discontinuation of DAPT after DES implantation within 1 year following the invasive procedure is not significantly associated with the risk of an occurrence of MACE during the follow-up.…”
Section: Adherence After Ami Treated By Pcimentioning
confidence: 99%
“…Harjai et al [44] in a prospective observation, demonstrated that the continuation of DAPT beyond 12 months in patients undergoing PCI of native coronaries, who survived with no major adverse cardiac events (MACE), did not confer long-term protection from death or myocardial infarction. Ferreira-Gonzales et al [45] has suggested that the discontinuation of DAPT after DES implantation within 1 year following the invasive procedure is not significantly associated with the risk of an occurrence of MACE during the follow-up.…”
Section: Adherence After Ami Treated By Pcimentioning
confidence: 99%
“…The details of the design of this registry have been described previously. 14 Demographic, clinical, and procedural data are collected in accordance with the American College of Cardiology National Cardiovascular Data Registry definitions and entered in an Excel spreadsheet. After discharge from the hospital, all patients are prescribed aspirin to be continued indefinitely.…”
Section: Guthrie Pci Registrymentioning
confidence: 99%
“…The impact of prolonged DAPT beyond 12 months has been evaluated in a registry study, which found no additional protection against death or MI compared with DAPT for ≤12 months. 84 This was confirmed in a randomised trial of continuing aspirin and clopidogrel versus monotherapy with aspirin in 2701 patients who had already received DAPT for 12 months after PCI. 85 At 2-years' follow-up, rates of MI and death were similar in the two groups (1.8% vs 1.2%), providing support for the guideline recommendation to continue DAPT for 12 months after PCI with DES.…”
Section: Stent Thrombosismentioning
confidence: 64%